1982
DOI: 10.2307/1129008
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Visual and Verbal Information in Children's Memories

Abstract: The extent to which children's visual memories were modified by subsequent verbal information was examined. In 2 experiments, 6-, 8-, and 10-year-old children and college students were asked questions after being shown slides. Some questions described events that appeared in the slides and other questions described events not depicted. In experiment 1 correct recall of the visual events was facilitated by congruent verbal information and impaired by incongruent verbal information. When subjects demonstrated go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
2
5

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 0 publications
1
38
2
5
Order By: Relevance
“…Deste modo, os adultos seriam menos sugestionáveis do que os adolescentes e estes menos sugestionáveis do que as crianças (Bruck & Ceci, 1999;Nurmoja, 2005). Porém, outros investigadores verificaram o oposto (e.g., Duncan, Whitney, & Kunen, 1982).…”
Section: Diferenças Individuais Na Sugestionabilidadeunclassified
See 2 more Smart Citations
“…Deste modo, os adultos seriam menos sugestionáveis do que os adolescentes e estes menos sugestionáveis do que as crianças (Bruck & Ceci, 1999;Nurmoja, 2005). Porém, outros investigadores verificaram o oposto (e.g., Duncan, Whitney, & Kunen, 1982).…”
Section: Diferenças Individuais Na Sugestionabilidadeunclassified
“…Resultados não concordantes com o acima descrito podem ser encontrados em estudos realizados por Duncan, Whitney, e Kunen (1982), Flin, Boon, Knox, e Bull (1992, citado em Baddeley, 1999 ou Finnila, Mahlberg, Santilla, Sandnabba, e Niemi (2003), entre outros. Nestes estudos, as faixas etárias abrangidas diferem, pois incluem a comparação com adultos (Duncan et al, 1982;Flin et al, 1992, citado em Baddeley, 1999 e apresentam descontinuidades etárias (comparação entre sete, nove, onze anos e adultos; seis, nove anos e adultos; quatro-cinco e sete-oito anos, respectivamente).…”
Section: Diferenças Individuais Na Sugestionabilidadeunclassified
See 1 more Smart Citation
“…Dessa forma, processos de plasticidade cerebral, responsáveis pelo fortalecimento de circuitos neurais, permitem com que diversos componentes e sistemas mnemônicos possam atingir melhor desempenho conforme a criança vai se desenvolvendo (Brehmer, Li, Müller, Von Oertzen, & Lindenberger, 2007). Essa melhora se dá tanto em relação aos componentes visuais quanto aos verbais (Duncan, Whitney, & Kunen, 1982). Esse fato pode ser devido ao tipo de processamento sensorial, no qual a percepção da criança se diferencia da do adulto, e não graças a diferenças em funções relacionadas com fatores cognitivos (Wilburn & Feeney, 2008).…”
Section: Desenvolvimento Da Memória: Da Primeira à Segunda Infância unclassified
“…Some researchers claimed that children's memories were not credible and were susceptible t o distortion (e.g., Messerschmidt, 1933;Pear & Wyatt, 1914;Stern, 1910). Other researchers disputed this claim, arguing that children were no less credible than adults (e.g., Duncan, Whitney, & Kunen, 1982;Flin, Boon, Knox, & Bull, 1992;Martin, Homes, Guth, & Kovac, 1979). However, several recent studies have suggested that young children are more susceptible to misleading information than adults (Ceci, Ross, & Toglia, 1987;King & Yuille, 1987;Oates & Shrimpton, 1991).…”
mentioning
confidence: 99%